Willingness of Women in Engineering towards the Purchase of Green Smartphone in Delhi NCR (India) - Dr. Prateek Gupta, Mr. Shashank Goel (International Journal of Advanced Science and Technology, 2019)
Purpose: The present research paper is worked out with a purpose to find out if there exists any relevant difference in the willingness of working and non-working women in engineering towards the purchase of green Smartphone.Design/ Methodology/ Approach: The research was conducted though a survey in order to develop an understanding about the willingness of women in engineering (both working and non-working women) towards the purchase of green Smartphone in Delhi NCR region of India. The data was collected from five major cities of National capital region viz. Gurgaon, Noida, Delhi, Ghaziabad and Meerut with the help of Questionnaire as a research tool.  Further, the data was analyzed and the hypothesis were tested using the two independent samples Mann-Whitney U test.Findings: The findings of the study revealed that though there may be lot of difference in working and non-working women in engineering with regards to various parameters such as income, working status, etc. but there is no relevant difference in the women’s willingness to purchase green smartphone. Limitations: The main limitation of the study is that the women respondents chosen for the study belongs to selected cities of Delhi National capital region and therefore, the geographical coverage is restricted to NCR.Practical Implications: The outcomes of the research study will enable marketers to have a better understanding of the women’s willingness to purchase green smartphone. The study will enable marketers to understand the willingness of women to purchase green smartphone in nearby future, willingness to purchase green smartphone despite of low budget, willingness to purchase green smartphone though it is complicated, willingness to purchase smartphone though already possessing one and willingness to purchase green smartphone for replacing the existing one. This will enable the marketers to understand the difference if any in working & non-working women’s buying behavior with regards to willingness to purchase green smartphone. The better understanding of the buying behavior enables marketers in formulation of right set of market strategies for grabbing a competitive position in the chosen target market.Originality/ Value: The present research work is the original work of the authors and the data collected for the study provides understanding about willingness of women in engineering towards purchase of green smartphone which enhances the understanding of organizations marketing smartphones and considering women as an important segment of the market. The research provides valuable insights that may enable marketers to focus on women consumers and frame right set of strategies. Article Type: Research Paper